Response to Callus Induction and Regeneration of Newly Released BRRI Rice Varieties - Joya, SD; Sultana, S; Ferdous, J; Qayum, MA; Hoque, ME (Bangladesh Rice Journal, 2020)
A study was carried out for developing an efficient callus induction and regeneration system for three newly developed BRRI varieties namely BRRI dhan86, BRRI dhan87 and BRRI dhan89. Dehusked seeds were plated onto MS and N6 media with two hormone combinations for callus induction. Calli obtained from each callus induction medium were transferred to four different regeneration media. Callus induction frequency and regeneration ability were significantly influenced by rice varieties, and interactions of variety and media. Among the media compositions, the highest callus (59.44%) were obtained from C1 (MS+2mg/l 2,4-D) followed by C2 ( MS+2 mg/l 2,4-D+0.5 mg/l kinetin) , C3 ( N6+2 mg/l 2,4-D) and C4 (N6+2 mg/l 2,4-D+0.5 mg/l kinetin) medium. The highest regeneration (45.74%) was obtained from R2 (MS+4 mg/ml BAP+1.2 mg/ml kinetin+0.5 mg/ml NAA), followed by R3 (1 mg/ml BAP+1 mg/ml Kinetin+1 mg/ml NAA), R4 (2 mg/ml kinetin+1 mg/ml NAA+300 mg casein hydrolysate) and R1 (2 mg/ml BAP+1 mg/ml kinetin+1 mg/ml NAA). BRRI dhan86 showed the highest regeneration ability (53.06%) than the other two varieties. It is observed that all varieties performed better in C1 medium for callus induction and R2 medium for regeneration. This study also revealed that BRRI dhan86 was more responsive to callus induction and regeneration of green plants than the other two varieties. Bangladesh Rice j. 2019, 23(2): 17-25